Percutaneous device embolization of an aneurysmal pulmonary artery in an infant weighing <3 kilograms. Issue 7 (29th April 2019) - Reynolds, Kathryn; Stapleton, Gary; Herbert, Carrie; Mauriello, Daniel
Abstract: Pulmonary artery aneurysm (PAA) and pulmonary artery pseudoaneurysm (PAP) are rare diagnoses in the pediatric population and carry a high risk of mortality if rupture occurs. There is currently no standard therapeutic approach to PAAs and PAPs. Reports of surgical intervention describe high mortality. We present a case of an infant with a PAP that was successfully treated with a percutaneous device closure. Our approach included deployment of a 6‐mm Amplatzer Vascular Plug 2 (Abbott, St. Paul, MN) in the right lower pulmonary artery segmental branch just proximal to the origin of the pseudoaneurysm. Subsequent imaging 1‐month post‐procedure demonstrated a >50% reduction in the size of the PAP when compared to original imaging studies and near‐complete resolution 14 months following the intervention. Percutaneous device placement to occlude the vessel supplying peripheral PAAs and PAPs may be a reasonable alternative to open surgical resection when treating patients with this rare, but potentially life‐threatening vascular anomaly. To our knowledge, this is the first case describing a successful device closure of a PAP in an infant weighing <3 kg.